Meaning in life as a predictor of the general health among medical sciences students: A cross‐sectional study - Zohreh Shahhosseini; Zeinab Hamzehgardeshi; Rahmatollah Marzband; Marzieh Azizi (Wiley, 2021)
Abstract Aim To investigate the predictive role of meaning in life on the general health among medical sciences students. Design A cross‐sectional study. Methods Four‐hundred medical sciences students were selected by proportional to size sampling. The general health questionnaire and the personal meaning profile were administrated to identify the predictive role of meaning in life on the student's general health. Descriptive statistics and linear regression were administrated. Results The mean ± SD of the total score of general health and meaning in life among students was 16.34 ± 6.73 and 71.50 ± 9.78, respectively. In the multiple linear regression model, factors such as father's educational level, and meaning in life can predict a 20% variance of general health among university students. As meaning in life thus emerges as a variable worth further in the health of university students, implementing interventional studies to assess the effect of meaning in life on students' general health is recommended.